Resistance Training Improves Quality of Life and Associated Factors in Patients With Fibromyalgia Syndrome - Sieczkowska S.M.* (2019)
© 2018 American Academy of Physical Medicine and RehabilitationBackground: Patients with primary symptoms of fibromyalgia (FM) have a lower quality of life than healthy people of the same age. The current treatment for FM is palliative, as there is no cure. Therefore, among strategies used to alleviate the symptoms, physical exercise has been recommended. Objective: To investigate the effects of a resistance training (RT) program on quality of life and associated factors in patients with FM. Design: Nonrandomized clinical trial. Brazilian Clinical Trials: http://www.ensaiosclinicos.gov.br/ (no. RBR-74pcmw). Participants: Forty-nine women with FM (mean age ± SD: 51.35 ± 9.34 years) allocated to an RT group (n = 26) or control group (CG; n = 23). Intervention: The intervention consisted of 4 weeks of a supervised RT program. Three, 60-minute, training sessions per week were conducted. Participants were evaluated before and after 4 weeks of exercise intervention. Main Outcome Measurements: The Fibromyalgia Impact Questionnaire was used to assess quality of life, and secondary outcomes were assessed with the Pittsburgh Sleep Quality Inventory, Beck Depression Inventory, and Beck Anxiety Inventory. The Wilcoxon test was used to verify the differences after 4 weeks of intervention (12 sessions) and the Mann-Whitney U test was used to compare the results for the RT group and CG. Results: The results demonstrated that 4 weeks of RT reduces the impact of FM on quality of life, depression, and anxiety (P <.05). Higher depression and anxiety scores were related to worsening quality of life. The CG did not show significant changes. Conclusions: RT reduces the impact of FM on the quality of life, and alleviates symptoms in women with FM. Level of Evidence: II [Correction added on June 21, 2019, after first online publication: Level of Evidence changed from I to II.].